Como regular la prueba pericial solicitada y practicada dentro del proceso con base en la articulación del código general del proceso (2014)
As is well known, the gaps are in the process of arbitration and not resolved in legal regulations as in these cases it is the law 1563 of 2012, will have to refer to the code of civil procedure take effect immediately from the general code of the process would have to refer to this. But well, what if in the process of arbitration there is any legal loophole and referring to the general code of the process (Law 1564, 2012) also have the ability to fill such a doubt? Most likely take effect immediately from the general code of the process is to generate such a problem, when you want to request an expert opinion and practice of profession within the process, which has reached out not in the procedural stage such as the filing of the claim or defense. Since the arbitration statute (Act 1563 of 2012) Article 31 does not regulate this issue specifically. How good was mentioned above and is known by all, at the time there in the arbitration process, a regulatory loophole will have to refer to the code of civil procedure take effect immediately from, the general code of the process. Which would generate great confusion since in general evidentiary matters not regulated process code specifically with relational expert evidence sought, enacted and practiced within the process. In this vein it is sought to achieve with this work to create opportunities for academic debate about the loopholes found in the arbitration statute and which can not find a solution in the general code of the process as an alternative source of such processes. At the same time you want to determine how although in practice it has not come to this type of situation because it has not been implemented fully the general code of the process can be through discussion of such issues find the solution this specific topic and enrich the knowledge to such processes